Meio Ambiente, Responsabilidade Social e Gorvenança Corporativa (ESG) - Gama, João Matheus Santos (Brasil, 2023)
The traditional company that focuses its activities only on showing profits Robustos is doomed to failure and has no place in the current sustainability scenario socioeconomic and environmental. Thus, we aim to analyze the importance of sustainability actions and business competitiveness. It is a search qualitative bibliographic nature of the descriptive and exploratory type with the use of material existing secondary and content analysis. The adoption of sustainable practices enables a series of business opportunities and constitutes a competitive differential. To the On the contrary, non-adherence to sustainable actions makes markets more restricted and decreases preference for choice on the part of consumers, who are increasingly adopting sustainable consumption. In addition, adherence enables cost reduction, improvement of company image, openness to new markets and raises the satisfaction of its employees, customers and other investors.